Gut microbiota influences feeding behavior via changes in olfactory receptor gene expression in Colorado potato beetles - Li, Hongwei; Yu, Yanxue; Zhang, Jian; Wang, Yuhan; Zhang, Liu; Zhai, Junfeng; Zhang, Yongjiang (Frontiers in Microbiology, 2023)
The Colorado potato beetle (CPB) is an internationally recognized plant quarantine pest that causes serious losses to potato agricultural production. The gut microbiota plays an important role in its growth and development, and the olfactory system plays an important role in insect feeding behavior. The gut microbiota is known to be capable of inducing changes in the olfactory systems of insects. However, the way these associated gut microbes influence the feeding-related behaviors of CPBs remains unclear. To explore the relationship between them, fresh potato leaves immersed in a mixture of five antibiotics (tetracycline, penicillin, ofloxacin, ciprofloxacin, and ampicillin) at specific concentrations for 1 h were fed to adult CPBs to reduce the abundance of gut microbes. We found that the feeding behavior of CPBs was significantly affected by the gut microbiota and that Pseudomonas was significantly higher in abundance in the control group than in the antibiotic group. We then used transcriptome sequencing to explore the differences in olfactory receptor genes in the heads of non-treatment and antibiotic-fed CPBs. Through Illumina Hiseq™ sequencing and screening of differential genes, we found that the olfactory receptor gene LdecOR9 was significantly upregulated and LdecOR17 was significantly downregulated after antibiotic feeding. A real-time polymerase chain reaction was used to verify the changes in olfactory receptor gene expression in the non-treatment groups and antibiotic-treated groups. The feeding behavior was partially rescued after CPBs were re-fed with intestinal bacteria. These results indicate that a certain amount of gut microbiota can result in the loss of the olfactory discrimination ability of CPBs to host plants. In summary, this study investigated the relationship between gut microbiota and olfactory genes, providing a reference for research on microbial control.